2021
DOI: 10.1016/j.yjsbx.2021.100045
|View full text |Cite
|
Sign up to set email alerts
|

Structural flexibility of the tetanus neurotoxin revealed by crystallographic and solution scattering analyses

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Recent studies on anti-TeNT humAbs reported that the highest TeNT neutralization was displayed by antibodies recognizing HC, particularly those preventing PSG binding, but did not report on HC-N recognition (39)(40)(41)(42). Although the role of HC-N in neuron intoxication is currently unknown, its deletion causes loss of toxicity (15).…”
Section: Humabs Recognize Distinct Domains Of Tent and Display Distinct Neutralizing Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on anti-TeNT humAbs reported that the highest TeNT neutralization was displayed by antibodies recognizing HC, particularly those preventing PSG binding, but did not report on HC-N recognition (39)(40)(41)(42). Although the role of HC-N in neuron intoxication is currently unknown, its deletion causes loss of toxicity (15).…”
Section: Humabs Recognize Distinct Domains Of Tent and Display Distinct Neutralizing Capabilitymentioning
confidence: 99%
“…The isolation of anti-TeNT humAbs from human B memory cells was recently reported (39)(40)(41)(42). TeNT neutralization in mice could be achieved only by preincubation of the toxin with a combination of 3 antibodies and/or using high molar excess of humAbs with respect to TeNT.…”
Section: The Structure Of the [Tent]-[tt104-fab]-[tt110-fab] Trimeric Immunocomplex Has Been Resolvedmentioning
confidence: 99%
“…Some of the X-ray crystallographic structures have been determined at acidic pH values in the range 4-6 [8], but no structural variation has been observed. Interestingly, BoNTs are closely related to the tetanus toxin TeNT, which presents a closed conformation with different organization, when compared to BoNT/E1 [11,12]. BoNT/A associates with the non-toxic non-hemagglutinin (NTNH) protein at acidic pH, forming stable complexes resistant to protease and acidic degradation [13].…”
Section: Introductionmentioning
confidence: 99%
“…The spatial localizations of the epitopes within the structure of TeNT were mapped to the crystallographic model [45,46] available in PDB (PDB: 1xdt) (Figure 4A), which displays the spatial location of the forty-three reactive epitopes identified by the SPOT synthesis array experiments (Table 1). Thirteen of the identified epitopes were exclusively in loop/coil structures while eleven shared amino acids in coil and helix or ß-sheet (Table 1 and Figure 4).…”
Section: The Spatial Location Of Tent Reactive Epitopesmentioning
confidence: 99%